Primary care consultations and costs among HIV-positive individuals in UK primary care 1995–2005: a cohort study. Issue 7 (22nd October 2009) - Evans, H E R; Tsourapas, A; Mercer, C H; Rait, G; Bryan, S; Hamill, M; Delpech, V; Hughes, G; Brook, G; Williams, T; Johnson, A M; Singh, S; et al.
Abstract : Objectives: To investigate the role of primary care in the management of HIV and estimate primary care-associated costs at a time of rising prevalence. Methods: Retrospective cohort study between 1995 and 2005, using data from general practices contributing data to the UK General Practice Research Database. Patterns of consultation and morbidity and associated consultation costs were analysed among all practice-registered patients for whom HIV-positive status was recorded in the general practice record. Results: 348 practices yielded 5504 person-years (py) of follow-up for known HIV-positive patients, who consult in general practice frequently (4.2 consultations/py by men, 5.2 consultations/py by women, in 2005) for a range of conditions. Consultation rates declined in the late 1990s from 5.0 and 7.3 consultations/py in 1995 in men and women, respectively, converging to rates similar to the wider population. Costs of consultation (general practitioner and nurse, combined) reflect these changes, at £100.27 for male patients and £117.08 for female patients in 2005. Approximately one in six medications prescribed in primary care for HIV-positive individuals has the potential for major interaction with antiretroviral medications. Conclusion: HIV-positive individuals known in general practice now consult on a similar scale to the wider population. Further research should be undertaken to explore how primary care can best contribute to improving the health outcomes of this group with chronic illness. Their substantial use of primary care suggests there may be potential to develop effective integrated care pathways.